Estudo genético e epigenético de fatores de risco materno para a síndrome de down - Mendes, Cristiani Cortez (2017)
Down syndrome (DS) results from failure in chromosomal segregation during maternal meiosis in about 90-95 % of the cases. The advanced maternal age at conception is considered the major risk factor for DS, however, many mothers of DS individuals are young, suggesting the existence of other etiological factors. Studies suggest that abnormal folate metabolism may cause hypomethylation of DNA pericentromeric, resulting in chromosomal nondisjunction. Moreover, genetic polymorphisms involved in folate pathway have been appointed as maternal risk factors for DS. Objectives: We compared the global DNA methylation between mothers of individuals with DS and mothers of individuals without the syndrome. We also investigated the impact of 18 polymorphisms involved in folate metabolism, and folate, homocysteine (Hcy) and methylmalonic acid (MMA) concentrations on the global DNA methylation. Finally, we evaluated the influence of thymidylate synthase (TYMS) 28-base pair (bp) repeats, TYMS 1494del6, DNA methyltransferase 3B (DNMT3B) -579G>T, DNMT3B -149C>T and DNMT3B -283T>C polymorphisms as maternal risk factors for DS and the association between these polymorphisms and the concentrations of folate, Hcy and MMA. Methods: One hundred and five mothers of individuals with free trisomy 21 and 185 mothers of individuals without the syndrome were included in this study. LINE-1 and Alu methylation were quantified by pyrosequencing. The TYMS 28-bp repeats polymorphism was performed by Polymerase Chain Reaction (PCR) using difference in the size of fragments; TYMS 1494del6 and DNMT3B -579G>T polymorphisms were analyzed by PCR followed by enzymatic digestion; and real-time polymerase chain reaction allelic discrimination was used for the genotyping of DNMT3B -149C>T and -283T>C polymorphisms. Data from the other polymorphisms were obtained from previously published articles by the research group. Plasma MMA and Hcy concentrations were determined by liquid chromatography-tandem mass spectrometry and serum folate by chemiluminescence. Results: LINE-1 methylation was lower in DS mothers than control mothers. Mothers with TCN2 776 CG and GG genotype present high Alu methylation and BHMT 742 GA and AA genotype were associated with low Alu methylation. Moreover, serum folate concentration was a predictor of LINE-1 methylation. Increased maternal risk for DS was associated with TYMS 3R/3R and DNMT3B -149TT/-283TC genotypes. In relation to metabolites, low Hcy concentration was observed in mothers with DNMT3B -149CT/-283CC genotypes when compared with the other combined genotypes. Conclusions: Reduced methylation of the LINE-1 sequence is a maternal risk factor for SD, as well as the TYMS 3R/3R genotype and the DNMT3B -149CT/-283CC combined genotypes. TCN2 776 CG and GG and BHMT 742 GA and AA genotypes modulate the Alu methylation. Serum folate is a predictor of the LINE-1 methylation and Hcy concentration is modulated by DNMT3B -149CT/-283CC combined genotypes in the studied population.